Involvement of l-Cysteine Desulfhydrase and Hydrogen Sulfide in Glutathione-Induced Tolerance to Salinity by Accelerating Ascorbate-Glutathione Cycle and Glyoxalase System in Capsicum - Cengiz Kaya; Bernardo Murillo-Amador; Muhammad Ashraf (MDPI AG, 2020)
The aim of this study is to assess the role of l-cysteine desulfhydrase (l-DES) and endogenous hydrogen sulfide (H2S) in glutathione (GSH)-induced tolerance to salinity stress (SS) in sweet pepper (Capsicum annuum L.). Two weeks after germination, before initiating SS, half of the pepper seedlings were retained for 12 h in a liquid solution containing H2S scavenger, hypotaurine (HT), or the l-DES inhibitor dl-propargylglycine (PAG). The seedlings were then exposed for three weeks to control or SS (100 mmol L−1 NaCl) and supplemented with or without GSH or GSH+NaHS (sodium hydrosulfide, H2S donor). Salinity suppressed dry biomass, leaf water potential, chlorophyll contents, maximum quantum efficiency, ascorbate, and the activities of dehydroascorbate reductase, monodehydroascorbate reductase, and glyoxalase II in plants. Contrarily, it enhanced the accumulation of hydrogen peroxide, malondialdehyde, methylglyoxal, electrolyte leakage, proline, GSH, the activities of glutathione reductase, peroxidase, catalase, superoxide dismutase, ascorbate peroxidase, glyoxalase I, and l-DES, as well as endogenous H2S content. Salinity enhanced leaf Na+ but reduced K+; however, the reverse was true with GSH application. Overall, the treatments, GSH and GSH+NaHS, effectively reversed the oxidative stress and upregulated salt tolerance in pepper plants by controlling the activities of the AsA-GSH and glyoxalase-system-related enzymes as well as the levels of osmolytes.